Amorphous random copolymers of lacOCA and manOCA for the design of biodegradable polyesters with tuneable properties. (September 2019) - Vagenende, Maxime; Graulus, Geert-Jan; Delaey, Jasper; Van Hoorick, Jasper; Berghmans, Francis; Thienpont, Hugo; Van Vlierberghe, Sandra; Dubruel, Peter
Graphical abstract: Abstract: Biodegradable polymers derived from renewable resources can be interesting materials for a plethora of applications and have therefore gained increased interest over the last decades. We herein report for the first time the synthesis of random copolymers based on lactic and mandelic acid via ring-opening-polymerisation of their corresponding O-carboxyanhydrides (OCA). Copolymers with tailored glass transition temperature and degradation time were obtained by adjusting the co-monomer feed during copolymerisation. Molecular weight analyses of the obtained copolymers indicated lower molecular weights in comparison to the target values. Our hypothesis that keto-enol tautomerisation of the OCA-monomers was the cause for this anomaly was substantiated by a mechanistic study of the OCA-polymerization reaction using lacOCA and manOCA as case study.